ANALISA DAN PERANCANGAN VIRTUAL LOCAL AREA NETWOORK (VLAN) PADA STMIK NEUMANN - Andalanta Sembiring (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
<pnalign=justify>VLAN is a logically separate network section. VLANs can be created using the method used for how different network segments are on routers with limited interfaces. In this thesis the author is to design a network that occurs at STMIK Kristen Neumann Indonesia. The application of VLAN can be applied using a LAN network so that the network can be safer at STMIK Kristen Neumann Indonesia. By using a VLAN network we can classify several LANs but within 1 LAN. with subneting for host restrictions. With this network division, it can directly improve LAN network security at STMIK Kristen Neumann Indonesia.